2022
DOI: 10.3390/healthcare10020346
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends of Asthma Mortality in China from 2000 to 2019: A Joinpoint Regression and Age-Period-Cohort Analysis

Abstract: Background: Trends of asthma mortality vary widely all over the world, while the trends in China over the past 15 years are unknown. The aim of this study was to assess the trends of asthma mortality in China. Methods: Asthma deaths and demographic characteristics were collected from National Death Cause Datasets of Disease Surveillance System between 2004 and 2019. The data were analyzed with joinpoint regression analysis and age-period-cohort (APC) analysis for the mortality rate due to asthma in China. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Children are more susceptible, which affects the incidence rate. The effects of age, period, and cohort on asthma mortality in Sichuan were not the same as those reported in Huang’s analysis of the long-term trends in asthma mortality in China from 2000 to 2019 [ 14 ]. Studies in Sichuan and China as a whole have shown that the age effect on asthma mortality increases with age, and the risk of mortality in later birth cohorts has generally decreased; however, the national period effect showed a V-shaped trend, which gradually decreased by period in Sichuan.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Children are more susceptible, which affects the incidence rate. The effects of age, period, and cohort on asthma mortality in Sichuan were not the same as those reported in Huang’s analysis of the long-term trends in asthma mortality in China from 2000 to 2019 [ 14 ]. Studies in Sichuan and China as a whole have shown that the age effect on asthma mortality increases with age, and the risk of mortality in later birth cohorts has generally decreased; however, the national period effect showed a V-shaped trend, which gradually decreased by period in Sichuan.…”
Section: Discussionmentioning
confidence: 72%
“…This may have contributed to asthma prevalence and the resulting substantial burden of disease [ 11 13 ]. Huang and his colleagues assessed trends in asthma mortality in China from 2000 to 2019, and showed that age, period, and population birth cohorts may contribute to changes in asthma mortality [ 14 ]. At present, the trends in asthma incidence and mortality in the western provinces of China are unclear.…”
Section: Introductionmentioning
confidence: 99%